Research on energy absorption characteristics of expanding anti-climber - XU Qinhua; GAO Xiaopeng; LIU Xudong; YU Mingyang; REN Pengfei; GUO Weinian (机车电传动)
In order to study the energy absorption characteristics of expanding anti-climber, the material performance of expanding pipes with different thicknesses were analyzed. The influence of different restraint methods on the average force value on simulated static pressure section was studied. Through the simulation and comparison of tests, the friction coefficients under the two matching relationships of pressure cones and expansion tube were obtained. Material tests at different strain rates were carried out to study the effects of high-speed impact force on the stable section in different hardening models, and the forces on the stable section at different impact speeds were analyzed based on the SHS hardening model. The results show that the material performance of expansion pipes with different thicknesses varies significantly and different boundary constraints significantly change the static pressure simulation force value. The friction coefficients are different between different pressure cones and expansion pipes, and the value of force increases with the increase of friction coefficient. The average forces on the stable section obtained by high-speed impact are basically the same in different hardening models. The force values of different impact speed on the simulated stable section are basically the same in SHS hardening model, and strain rate effect only shows at the initial stage of the impact. Adopting 1/4 simplified model can significantly improve the calculation efficiency without compromising the calculation accuracy.